2009
DOI: 10.1016/j.matlet.2009.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Self-aligned and bundled electrospun fibers prepared from blends of polystyrene (PS) and poly(methyl methacrylate) (PMMA) with a hairy-rod polyphenylene copolymer

Abstract: Bundled and self-aligned fibers were obtained by electrospinning blends of polystyrene (PS) and poly (methyl methacrylate) (PMMA) with a hairy-rod polyphenylene-g-polystyrene/poly(a-caprolactone) (PP-g-PS/PCL) copolymer. The self-alignment and bundling characteristics of these electrospun fibers were ascribed to the unique molecular architecture of the conjugated polymer, PP-g-PS/PCL, and its interactions with the solvent and the polymer matrixes used for the electrospinning. The self-alignment and bundling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The alignment of the electrospun fibers was observed in both cases, but the alignment of the electrospun fibers including PS was better than that of the electrospun fibers including PMMA. They confirmed that the phenomenon was closely related to the electric properties of the polymers [20]. Figure 6i shows the full width at half maximum (FWHM) values for the various concentrations of SF; increasing the concentration of SF contributes to the alignment of the electrospun biocomposites.…”
Section: Resultssupporting
confidence: 57%
“…The alignment of the electrospun fibers was observed in both cases, but the alignment of the electrospun fibers including PS was better than that of the electrospun fibers including PMMA. They confirmed that the phenomenon was closely related to the electric properties of the polymers [20]. Figure 6i shows the full width at half maximum (FWHM) values for the various concentrations of SF; increasing the concentration of SF contributes to the alignment of the electrospun biocomposites.…”
Section: Resultssupporting
confidence: 57%
“…26 The degree of fiber alignment increased with the electrical conductivity of the polymer solution. 27 A quantitative orientation factor, f ¼ (90 À / 0 )/90 was calcu-lated from FWHM (/ 0 ) of the orientation distribution of the PCL/SIS fibers made with various concentrations of SIS. This orientation factors were 0.3, 0.47, 0.54, and 0.56 for PCL, PCL/SIS-I, PCL/SIS-II, and PCL/SIS-IIII, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The amphipolar character was previously confirmed by electrospining investigations of the blends of this copolymer with PSt and poly(methyl methacrylate) (PMMA). 81 The selfalignment and bundling characteristics observed for the obtained fibers were ascribed to the unique molecular architecture of this PPP and its peculiar interactions with the solvents and polymer matrix used for electrospinning.…”
Section: ■ Results and Discussionmentioning
confidence: 94%